The effect of pergolide mesylate on adrenocorticotrophic hormone responses to exogenous thyrotropin releasing hormone in horses. (July 2022) - Durham, A.E.
Abstract: Thyrotropin releasing hormone (TRH) stimulation testing is often used to support a diagnosis of pituitary pars intermedia dysfunction (PPID) in horses although it is unclear whether or not repeat TRH stimulation testing post-treatment is a valid means of assessing response to medical therapy. Laboratory submissions from 64 suspected equine PPID cases were examined including the initial pre-treatment TRH stimulation test and a follow up test within 100 days of starting medical therapy with pergolide. In a subset of cases, further follow-up tests were examined beyond 100 days of starting treatment. Results from tests conducted between 1 July and 30 November were excluded. Significant improvements were seen in both the baseline and TRH-stimulated adrenocorticotrophic hormone (ACTH) concentrations within 100 days with no further improvements seen in the subset of cases examined thereafter. Although 88% ( n = 56/64) of all cases showed a decreased response to TRH post-treatment, only 24% ( n = 9/38) of horses with positive pre-treatment TRH stimulation tests normalised following treatment, with a further 34% ( n = 13/38) improving into an equivocal test outcome category. Most commonly (42%; n = 16/38), horses with positive pre-treatment TRH stimulation tests remained positive following treatment, although 75% ( n = 12/16) of these showed a numerically lower post-treatment response to TRH. These results will help inform practitioners of expected changes in TRH stimulation test results when assessing response of horses with PPID to medical therapy with pergolide. Highlights: Baseline adrenocorticotropin (ACTH) improved within 100 days of pergolide treatment. Thyrotropin releasing hormone (TRH) responses also improved following treatment. 88% of all cases showed a decreased response to TRH post-treatment. 24% cases with positive TRH stimulation tests normalised following treatment. 34% cases with positive TRH stimulation tests became equivocal following treatment.